Living up to the Hype of Hyperspectral Aquatic Remote Sensing: Science, Resources and Outlook - Dierssen, Heidi M.; Ackleson, Steven G.; Joyce, Karen E.; Hestir, Erin L.; Castagna, Alexandre; Lavender, Samantha; McManus, Margaret A. (Frontiers in Environmental Science, 2021)
Intensifying pressure on global aquatic resources and services due to population growth and climate change is inspiring new surveying technologies to provide science-based information in support of management and policy strategies. One area of rapid development is hyperspectral remote sensing: imaging across the full spectrum of visible and infrared light. Hyperspectral imagery contains more environmentally meaningful information than panchromatic or multispectral imagery and is poised to provide new applications relevant to society, including assessments of aquatic biodiversity, habitats, water quality, and natural and anthropogenic hazards. To aid in these advances, we provide resources relevant to hyperspectral remote sensing in terms of providing the latest reviews, databases, and software available for practitioners in the field. We highlight recent advances in sensor design, modes of deployment, and image analysis techniques that are becoming more widely available to environmental researchers and resource managers alike. Systems recently deployed on space- and airborne platforms are presented, as well as future missions and advances in drone technology and autonomous in-water survey methods. These systems will greatly enhance the ability to collect interdisciplinary observations on demand and in previously inaccessible environments. Looking forward, the advances in sensor miniaturization are discussed alongside the incorporation of citizen science, moving towards open and FAIR (findable, accessible, interoperable, and reusable) data. Also, advances in machine learning and cloud computing allow for exploitation of the full electromagnetic spectrum, and better bridging across the larger scientific community that additionally includes biogeochemical modelers and climate scientists. These advances will place sophisticated remote sensing capabilities into the hands of individual users and provide on-demand imagery tailored to research and management requirements, as well as provide critical input to marine and climate forecasting systems. The next decade of hyperspectral aquatic remote sensing is on the cusp of revolutionizing the way we assess and monitor aquatic environments and detect changes relevant to global communities.